Exploration of Language Functions as an Ideological State Apparatus in the Novel Lord of the Flies (Journal of Social Sciences Review, 2023)
William Golding's novel "Lord of the Flies" explores the role of language in shaping societal norms, values, and power structures. The language used by the characters reflects their respective ideologies and contributes to the development of their positions. Language also reveals power dynamics and social hierarchies within the group, with characters who speak Standard English portrayed as more intelligent and civilised. The use of language perpetuates the dominant ideology of the group, with Jack using aggressive language to exert control over others while Ralph employs more collaborative and inclusive language. This paper demonstrates how language is not merely a means of communication but a tool for shaping and reinforcing societal norms, values, and power structures. Using language as an ideological state apparatus plays a significant role in shaping the characters' ideological positions and the dynamics within the group.
Keywords: Language; Characters; Lord of the Flies; Social Ideology